2022
DOI: 10.1111/jce.15573
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of atrial low voltage induced by vein of Marshall ethanol infusion

Abstract: Introduction Systematic and quantitative descriptions of vein of Marshall (VOM)‐induced tissue ablation are lacking. We sought to characterize the distribution of low voltage observed in the left atrium (LA) after VOM ethanol infusion. Methods and Results The distribution of ethanol‐induced low voltage was evaluated by comparing high‐density maps performed before and after VOM ethanol infusion in 114 patients referred for atrial fibrillation ablation. The two most frequently impacted segments were the inferior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The regions intervened by ethanol was dependent on the anatomical distribution of the branches of the VOM. 18 (2) The connections between VOM and left PV: There are abundant junctions between VOM and left PV. Some of the branching courses of the VOM insert into the PV directly from epicardial access.…”
Section: Discussionmentioning
confidence: 99%
“…The regions intervened by ethanol was dependent on the anatomical distribution of the branches of the VOM. 18 (2) The connections between VOM and left PV: There are abundant junctions between VOM and left PV. Some of the branching courses of the VOM insert into the PV directly from epicardial access.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the limitations of VOM ethanol infusion, we should be cautious about its utility in PeAF ablation. Firstly, the anatomical course of the VOM determines the lesion sites and VOM ethanol infusion areas [ 48 ]. Based on this, the mitral annular side of the MI is usually beyond the lesion region of VOM ethanol infusion ( Figure 4 G,H).…”
Section: The Limitations Of Vom Ethanol Infusionmentioning
confidence: 99%
“…It is one of the most important findings of this study that successful VOM ethanol infusion in conjunction with radiofrequency ablation within the CS (in all patients) was able to achieve bidirectional block of the mitral isthmus in 97%, a result that virtually promises a guarantee of bidirectional block of the most challenging linear lesion in the human atria. The strength of the presented study by Kamakura et al 9 is that it provides important new data on the distribution of lesion sets specifically induced by VOM ethanol infusion in a large cohort of patients with persistent AF. Moreover, the authors identified a distinct fingerprint lesion pattern of VOM ethanol infusion that is observed in almost all patients undergoing successful VOM ethanol infusion.…”
mentioning
confidence: 93%
“…The strength of the presented study by Kamakura et al 9 is that it provides important new data on the distribution of lesion sets specifically induced by VOM ethanol infusion in a large cohort of patients with persistent AF. Moreover, the authors identified a distinct fingerprint lesion pattern of VOM ethanol infusion that is observed in almost all patients undergoing successful VOM ethanol infusion.…”
mentioning
confidence: 93%
See 1 more Smart Citation